Klasifikasi Citra Dalam Identifikasi Jeruk Nipis dan Jeruk Mandarin Menggunakan Convolutional Neural Network (CNN) - Saputra, Randy; Erlanda, Hadrian; Ramadhanu, Agung (SOTVI - Society of Visual Informatics, 2024)
With the rapid development of technology in the field of image processing, it really helps farmers in identifying types of citrus fruit. This research aims to identify the differences between limes (Citrus aurantiifolia) and mandarin oranges (Citrus reticulata) using image processing methods and morphological analysis. Image processing is carried out to analyze visual differences based on color, texture and fruit size. In addition, chemical analysis was carried out to differentiate the composition of the compounds contained in the two types of oranges. The research results show that this approach is able to identify the differences between limes and mandarins with a high level of accuracy, and can be applied in various industries, including agriculture and food processing.